2021
DOI: 10.14309/ctg.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Tumor Burden Correlates With Tumor Budding and Poorly Differentiated Clusters: A New Prognostic Factor in Colorectal Carcinoma?

Abstract: INTRODUCTION: Molecular lymph node (LN) staging in early colorectal cancer (CRC) has demonstrated to be more precise than conventional histopathology pN staging. Tumor budding (TB) and poorly differentiated clusters (PDCs) are associated with LN metastases, recurrences, and lower survival in CRC. We evaluated the correlation between the total tumor load (TTL) in LNs from CRC surgical specimens with patient outcome, TB, and PDC. METHODS: In this retrospective multicentre stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…Significant tumor volume and lymphatic tumor dissemination likely reduce the chances of achieving maximal tumor response as well as reflect poor prognosis. 42,43 Absence of significant difference in achieving pCR by using different radiation techniques or chemotherapy protocols has been reported in previous trials and was repeated in our study as well showing the 33.7% pCR rate in node negative disease compared with 21.3% in node positive patients. 14,44,45 At the time of surgery, 9 (3.1%) patients were upstaged to metastatic after resection of suspicious hepatic lesions and continued with appropriate treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Significant tumor volume and lymphatic tumor dissemination likely reduce the chances of achieving maximal tumor response as well as reflect poor prognosis. 42,43 Absence of significant difference in achieving pCR by using different radiation techniques or chemotherapy protocols has been reported in previous trials and was repeated in our study as well showing the 33.7% pCR rate in node negative disease compared with 21.3% in node positive patients. 14,44,45 At the time of surgery, 9 (3.1%) patients were upstaged to metastatic after resection of suspicious hepatic lesions and continued with appropriate treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Accordingly, different OSNA studies in breast SLN have set cut-off values in order to predict the axillary LN status; some of which (10,000–15,000 copies) are already included in clinical guidelines [ 52 , 53 ]. In 2017, Rakislova et al [ 54 ] explored its utility to predict recurrences in colorectal carcinoma, and a recent study confirmed that a TTL ≥ 6000 copies/μl was associated with worse disease free survival in those patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, different OSNA studies in breast SLN have set cut-off values in order to predict the axillary LN status; some of which (10,000-15,000 copies) are already included in clinical guidelines [52,53]. In 2017, Rakislova et al [54] explored its utility to predict recurrences in colorectal carcinoma, and a recent study con rmed that a TTL ≥ 6,000 copies/µl was associated with worse disease free survival in those patients [55].…”
Section: Discussionmentioning
confidence: 99%